2021
DOI: 10.1016/j.japh.2020.07.022
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of online pharmacies selling Adderall

Abstract: Objectives: Adderall (amphetamine-dextroamphetamine) is a controlled substance with harmful adverse effects if abused or misused. We assessed the availability of Adderall from common search engines, and evaluated the safety and marketing characteristics of online pharmacies selling Adderall. Design: Cross-sectional study. Setting and participants: From December 2019 to February 2020, the phrase "buy Adderall online" was queried in four search engines: Google (N ¼ 100), Bing (N ¼ 100), Yahoo (N ¼ 50) and DuckDu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 24 publications
2
11
0
Order By: Relevance
“…Most of the illegitimate online pharmacy websites analyzed in this study (75/82, 92%) hosted their servers in a country different from that listed on their website. This is in line with other studies that have reported similar differences in server and listed locations [ 35 ]. Although this difference does not verify that online pharmacies’ physical locations are different from what are reported, it does raise the concern that many of these pharmacies are misleading patients by reporting to be located in one country but are actually dispensing from another country.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Most of the illegitimate online pharmacy websites analyzed in this study (75/82, 92%) hosted their servers in a country different from that listed on their website. This is in line with other studies that have reported similar differences in server and listed locations [ 35 ]. Although this difference does not verify that online pharmacies’ physical locations are different from what are reported, it does raise the concern that many of these pharmacies are misleading patients by reporting to be located in one country but are actually dispensing from another country.…”
Section: Discussionsupporting
confidence: 93%
“…Prior studies have suggested that the cost of medications online vis-à-vis brick-and-mortar stores differs depending on the product [34][35][36][37]. Here, we report similar findings.…”
Section: Medicine Pricessupporting
confidence: 88%
“…Beyond concerns related to medication quality, there is also concern regarding the lack of services offered by illegitimate internet pharmacies [ 15 ]. In choosing illegitimate internet pharmacies, patients opt out of medication counseling, monitoring, and drug-drug interactions checking that pharmacists and other health care professionals provide to ensure proper medication use [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thanks to many studies aimed at identifying the cause of widespread illegal Internet pharmacies, such as the scientific work of Vida et al [ 20 ] or Penley et al [ 21 ], the global pharmaceutical community has concluded that online surveillance bodies need to be improved.…”
Section: Discussionmentioning
confidence: 99%